OPPORTUNISTIC BACTERIA IN AGROECOSYSTEMS OF UKRAINE - Butsenko, L. M.; Pasichnyk, L. A. (International Journal of Medicine and Medical Research, 2018)
Background. Recently, the number of diseases caused by opportunistic bacteria has been increasing all over the world. Opportunistic microorganisms are characterized by ubiquitous proliferation, flexibility in adaptation to the conditions of the environment, lack of specific relationship with the macroorganism. Phytopathogenic bacteria are also able to infect both plants and animals. Objective. The purpose of the research was to detect the Pantoea agglomerans and Pseudomonas fluorescens bacteria in various ecological niches and establish their virulence. Methods. Classical microbiological, biochemical, serological methods were used in the research. The identification of bacteria was carried out according to their phenotypic properties. Results. It has been established that opportunistic bacteria species P. agglomerans and P. fluorescens are present in wheat agrophytocenoses. The bacteria isolated from the agrophytocenoses are virulent for wheat, rye and weed plants. Antibodies to opportunistic bacteria, which are spread in agrophytocenoses of cereals crops, have been found in the blood of healthy rabbits. Conclusions. Thus, we have established that virulent strains of opportunistic bacteria P. agglomerans and P. fluorescens are spread in agrophytocenoses of cereals. The presence of antibodies to these bacteria in the blood of healthy rabbits proves that opportunistic bacteria from plant material get into animals and humans. Knowledge of biology and the spread of opportunistic pathogens in agrophytocenoses is necessary for prevention of infections that these bacteria cause in humans.